An Analysis of Ideology Application in Translating Next Novel: A Translation Strategy - Syamsurrijal Syamsurrijal; Fitri Arniati (Lingua Susastra, 2023)
Ideology is considered very important in various disciplines including translation studies. Ideology and its influence on translation have long been the focus of research in the field of translation studies. The purpose of writing this article is to know and understand the ideology used by translators in translating Michael Crichton's novel The Next. The research methodology is descriptive qualitative by reading, understanding and comparing the novel The Next in English with the novel The Next translated in Indonesian. Data was obtained by identifying each word, phrase, clause, and sentence in Next's novel. Data analysis by classifying the data obtained based on Newmark's theory (1988). He classifies the word culture into five categories in his book Translated Textbook, namely: (a) ecology, (b) cultural material, (c) socio-cultural, (d) the name of the organization, (e) gestures and customs. This study found 157 cultural categories consisting of 55 Material Culture, 18 Socio-Cultural, 48 Social Organization, 23 Ecology, 6 Habits and 17 Other Cultures.